The Function of Happiness on Weakening and Strengthening Depressive Effect on Academics’ Suicidal Ideation - Darmayanti, Kusumasari Kartika Hima; Anggraini, Erlina; Winata, Efan Yudha; Purwasih, Inda; Fakhriya, Siti Dini (UI Scholars Hub, 2022)
Year to year, the suicide rate among academics in Nusa Tenggara Barat Province has risen because of various factors. Suicidal behavior results from suicidal ideation, which is triggered by negative emotions that cause psychological stress, such as depression. On the other hand, numerous previous studies found a contribution of happiness and depression to suicidal ideation. Hence, this study examined the significance of the role of happiness in moderating the effect of depression on suicidal ideation. Further, this was a survey study on academics in Nusa Tenggara Barat Province (n = 182). Moderator analysis was applied in this study using the PROCESS Macro version 3.0 installed in the IBM SPSS 23.00. The study’s findings have shown that happiness significantly moderates the effect of depression on suicidal ideation. The happier the person is, the lesser the depression impacts suicidal ideation. Moreover, these findings suggest that clinical psychologists working with academic clients should pay attention to increasing happiness as a resource for psychological interventions to reduce the severity of depression’s effect on suicidal ideation.